2008
DOI: 10.1084/jem.20080789
|View full text |Cite
|
Sign up to set email alerts
|

Human PMS2 deficiency is associated with impaired immunoglobulin class switch recombination

Abstract: Ig class switch recombination (CSR) defi ciencies are rare primary immunodefi ciencies characterized by normal or increased serum IgM levels and a contrasting, marked decrease or absence of IgG, IgA, and IgE. As a result of this molecular defect, defective CSR may be associated with faulty generation of somatic hypermutations (SHMs) in the Ig variable (V) region. The molecular identifi cation and analysis of several CSR defi ciencies has made it possible to better describe the mechanisms underlying CSR and SHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
107
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 31 publications
7
107
2
3
Order By: Relevance
“…Although the present study and previous work have shown that PMS2 plays a role in postreplicative MMR and in the repair of double-stranded DNA breaks in Ig switching regions, deficiency of the protein has a modest or no effect during SHM of the Ig locus (16)(17)(18)(19). Considering the possibility that other factors (e.g., MLH3 or apurinic/apyrimidinic endonuclease) might efficiently compensate for the absence of PMS2 and fulfill the endonucleolytic requirements of V-region hypermutation, we investigated SHM in our mutant mice.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…Although the present study and previous work have shown that PMS2 plays a role in postreplicative MMR and in the repair of double-stranded DNA breaks in Ig switching regions, deficiency of the protein has a modest or no effect during SHM of the Ig locus (16)(17)(18)(19). Considering the possibility that other factors (e.g., MLH3 or apurinic/apyrimidinic endonuclease) might efficiently compensate for the absence of PMS2 and fulfill the endonucleolytic requirements of V-region hypermutation, we investigated SHM in our mutant mice.…”
Section: Resultscontrasting
confidence: 73%
“…Indeed, our Pms2 −/− mice had Sμ-Sγ3 junctional DNA segments with extended microhomology (≥5 nts) and a longer average length compared with WT mice (5.07 ± 1.4 vs. 2.6 ± 0.44; P = 0.04) ( Table 1). Abnormal formation of switch junctions also has been identified in truncated forms of human PMS2 (16). In contrast, although we detected a tendency toward a preferential use of blunt junctions in Pms2 EK/EK mice compared with WT mice (Table 1), we found no significant differences in the relative frequencies of the different types of junctions (i.e., blunt junctions, microhomologies, or insertions) or in the average length of microhomology (2.54 ± 0.53 vs. 2.6 ± 0.44; P = 0.47) between the Pms2 EK/EK and the WT mice (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of the DNA repair pathway for S region end-joining is made at the start of the CSR process (i.e., as soon as DNA lesions have been induced). We chose to analyze Sμ-Sα junctions because these junctions are known to be strongly affected by deficiencies in DNA ligase 4 or PMS2, in contrast to Sμ-Sγ junctions, which are little influenced by these deficiencies (17,31). We also attempted to amplify Sμ-Sα junctions from homozygous AIDdeficient (AID −/− ) patients but failed, most likely due to the complete absence of CSR in these patients (1).…”
Section: Position Of Sμ and Sα Breakpoints In Switchmentioning
confidence: 99%
“…Interestingly, AID, UNG, and PMS2 involved in the generation of DNA lesions or breaks seem to exert further activity during S region end-joining. Why microhomology-mediated repair occurs in PMS2-deficient cells remains unclear (31,41). A recent study with PMS2 endonuclease-deficient mice indicated that the presence of the PMS2 protein, but not its endonuclease activity, was required for proper S region end-joining, but that PMS2 endonuclease activity was still necessary for efficient CSR (42).…”
Section: Position Of Sμ and Sα Breakpoints In Switchmentioning
confidence: 99%